The micro-LED roadmap: status quo and prospects - Chien-Chung Lin; Yuh-Renn Wu; Hao-Chung Kuo; Matthew S Wong; Steven P DenBaars; Shuji Nakamura; Ayush Pandey; Zetian Mi; Pengfei Tian; Kazuhiro Ohkawa; Daisuke Iida; Tao Wang; et al. (JPhys Photonics, 2023)
Micro light-emitting diode (micro-LED) will play an important role in the future generation of smart displays. They are found very attractive in many applications, such as maskless lithography, biosensor, augmented reality (AR)/mixed reality etc, at the same time. A monitor that can fulfill saturated color rendering, high display resolution, and fast response time is highly desirable, and the micro-LED-based technology could be our best chance to meet these requirements. At present, semiconductor-based red, green and blue micro-LED chips and color-conversion enhanced micro-LEDs are the major contenders for full-color high-resolution displays. Both technologies need revolutionary ways to perfect the material qualities, fabricate the device, and assemble the individual parts into a system. In this roadmap, we will highlight the current status and challenges of micro-LED-related issues and discuss the possible advances in science and technology that can stand up to the challenges. The innovation in epitaxy, such as the tunnel junction, the direct epitaxy and nitride-based quantum wells for red and ultraviolet, can provide critical solutions to the micro-LED performance in various aspects. The quantum scale structure, like nanowires or nanorods, can be crucial for the scaling of the devices. Meanwhile, the color conversion method, which uses colloidal quantum dot as the active material, can provide a hassle-free way to assemble a large micro-LED array and emphasis the full-color demonstration via colloidal quantum dot. These quantum dots can be patterned by porous structure, inkjet, or photo-sensitive resin. In addition to the micro-LED devices, the peripheral components or technologies are equally important. Microchip transfer and repair, heterogeneous integration with the electronics, and the novel 2D material cannot be ignored, or the overall display module will be very power-consuming. The AR is one of the potential customers for micro-LED displays, and the user experience so far is limited due to the lack of a truly qualified display. Our analysis showed the micro-LED is on the way to addressing and solving the current problems, such as high loss optical coupling and narrow field of view. All these efforts are channeled to achieve an efficient display with all ideal qualities that meet our most stringent viewing requirements, and we expect it to become an indispensable part of our daily life.